Analisis Fatwa Ulama Indonesia dalam Menyikapi Pandemi Corona Virus 2019 - Bahrul Muttakin; Abd. Hadi (JOSH: Journal of Sharia, 2024)
The COVID-19 pandemic has not ended yet; in fact it mutated and gave rise to a new variant which was later known as omicron. COVID-19 has threatened various sectors of life including religious life; religious rituals during the pandemic are limited and must follow health protocols to avoid the spread of the virus. Religious authorities play an important role in responding to this situation, including in issuing fatwas regarding guidelines for the implementation of worship during the COVID-19 period. Therefore, this article discusses the guidelines for the implementation of worship issued by these religious authorities. The focus of this article is to compare the fatwas of religious authorities regarding guidelines for the implementation of worship during the COVID-19 period; the fatwas referred to here are limited to the fatwas of the Indonesian Ulema Council (MUI), the fatwas of the Majlis Tarjih Muhammadiyah, and the fatwas of Lajnah Bahsul Masail Nahdlatul Ulama. This research is a library research with a comparative descriptive approach. The results of the study show that the fatwas related to the guidelines for the implementation of worship during the pandemic issued by the three religious authorities synergize, cooperate with and support each other in dealing with the COVID-19 pandemic. Unlike MUI and Nahdlatul Ulama, Muhammadiyah responded with concrete actions, namely establishing the Muhammadiyah COVID-19 Command Center (MCCC) with the main task of coordinating various programs in the context of dealing with the COVID-19 pandemic.